Serum uric acid as a diagnostic biomarker for preeclampsia: comparison with renal indices and cerebroplacental ratio - Chen, Xiaoyan; Lian, Kaimei (Frontiers in Endocrinology, 2026)
ObjectiveTo investigate the diagnostic performance of renal function-related indices (blood urea nitrogen (BUN), serum creatinine (sCr), serum uric acid (sUA), serum cystatin C (sCys C)) and the cerebroplacental ratio (CPR) for preeclampsia (PE).MethodsIn a retrospective case-control design, we reviewed the medical records of 172 pregnant women (84 with PE and 88 normotensive controls) who delivered between 2021 and 2024. Independent risk factors were identified using logistic regression, and the Receiver Operating Characteristic (ROC) curve analysis was used to assess the discriminative ability of each parameter for detecting PE.ResultsCompared with healthy controls, women with PE exhibited elevated sUA concentrations, greater pre-pregnancy body mass index (BMI), and lower CPR values (all P < 0.05). Multivariable analysis confirmed sUA as an independent predictor of PE, with a substantially increased odds ratio (OR) of 14.082 (P < 0.001). ROC curve analysis revealed that sUA had the highest area under the curve (AUC) for diagnosing PE (AUC = 0.837; 95% CI: 0.775-0.899), with a sensitivity of 75.00% and a specificity of 84.09%.ConclusionAmong the multiple renal function indices studied, sUA demonstrates the best diagnostic performance for PE and could serve as an effective biomarker for the clinical assessment of PE risk.